2021
DOI: 10.1021/acs.cgd.1c00569
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Shape Evolution of Selective Area Grown Zn3P2 Nanoislands

Abstract: Selective area growth of zinc phosphide (Zn3P2) on InP provides a pathway to high-quality semiconductor nanostructures and textured thin films made of earth-abundant elements. In the precoalescence stage, Zn3P2 emerges in the form of nanoislands undergoing a peculiar shape transformation in the course of growth. We present a model based on the minimization of the surface energy with respect to the relevant geometrical parameters which quantitively describes the shape of nanoislands depending on their volume. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The morphology of the nanostructure is a function of the shape of the hole. Nanopyramids are the result for circular holes, while nanowires, or even nanowire networks, are achieved from elongated slits as shown in Figure . However, these shapes are only observed after a couple of intermediate stages. The intermediate morphology as zinc phosphide outgrows the hole depends on the relative surface energies of the dominating facets, namely, (001), (112), and (101).…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The morphology of the nanostructure is a function of the shape of the hole. Nanopyramids are the result for circular holes, while nanowires, or even nanowire networks, are achieved from elongated slits as shown in Figure . However, these shapes are only observed after a couple of intermediate stages. The intermediate morphology as zinc phosphide outgrows the hole depends on the relative surface energies of the dominating facets, namely, (001), (112), and (101).…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
“…The intermediate morphology as zinc phosphide outgrows the hole depends on the relative surface energies of the dominating facets, namely, (001), (112), and (101). DFT calculations showed that E (101) < E (112) < E (001) . ,, The morphology evolution can be determined through a dimensionless geometric parameter based on the relative surface energies and initial hole size . The facet fractions and shape evolution based on this model are shown in Figure .…”
Section: Growth and Crystalline Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The growth of III−V and III-N NWs by selective area epitaxy (SAE) on masked substrates with regular arrays of pinholes [4][5][6][7][8][9][10][11] allows one to synthesize NW ensembles uniform in size with exactly determined positioning of NWs and distances between them. The SAE technique is also used to synthesize nanomembranes [12,13] and nanoislands [14] of various geometry. These structures hold much promise for application in nanophotonics and nanoelectronics with an option for integration into silicon electronic technology.…”
mentioning
confidence: 99%